Biological cycle of the greater wax moth Galleria mellonella (Linnaeus, 1758) (Lepidoptera: Pyralidae: Galleriinae) in Panama - Alex Ríos-Moreno (Revista Chilena de Entomología)
The greater wax moth Galleria mellonella (Linnaeus, 1758), is one of the principal pests in the honeycomb of the European bee Apis mellifera Linnaeus, 1758, around the world. In this experiment, the complete biological cycle of G. mellonella was determined for the first time in Panama, achieving an incubation period of 4 to 10 days with an average of 7.16 ± 1.42. The larvae went through eight larval instars with a total larval duration of ±38.63 days. The pupa period was 9.22 ± 1.40 days. The average daily oviposition varied from a maximum of 182 to a minimum of 1.8 eggs, and the maximum life span of the adult was eight days. The number of eggs hatched was 1,503 in 10 evaluation days; on day 7, the most hatching occurred with 410 newly emerged larvae. The temperature and relative humidity averages were 28 °C and 76%, respectively, and varied from 25-33 °C to 58%-86% during the evaluation period. The life cycles of females and males were similar, of 39.00 and 39.53 days, respectively. The artificial diet used in this study guaranteed the successful completion of the larval stage in the life cycle of this wax moth.